Analysis of Performance on Ultra Wideband Circular Patch for Solar Cell Antenna Design - Hamid H.A.S.; Chin Hock G.; Ferdous N.; Rahman M.N.A. (Institute of Physics Publishing, 2023)
Bandwidth; Data transfer rates; Energy conservation; Environmental technology; Esters; Polyimides; Polymer matrix; Slot antennas; Solar cells; Substrates; Ultra-wideband (UWB); Antenna design; Bandwidth performance; Circular microstrip patch; Circular patch antenna; CST microwave studio; Materials design; Research analysis; Research studies; Microstrip antennas